EVALUASI PELAYANAN DESA MELALUI WEBSITE GIGADES.ID DI DESA PULAU BANJAR KARI KABUPATEN KUANTAN SINGINGI TAHUN 2023 - Nuraini, Ika; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Gigades.id is a digital platform developed by PT. Phoenix Kreatif Digital to improve the quality of village services through information technology. This website serves as an online public service medium that facilitates community access to information and document processing. This study aims to describe the evaluation of village services through the Gigades.id website in Pulau Banjar Kari Village in 2023. The study uses a descriptive qualitative approach with data collected through interviews and documentation. The findings show that in the context aspect, the website aligns with the digital service needs, but the readiness of village officials and the community is still low. In the input aspect, the main obstacles include limited human resources, lack of training, and minimal budget allocation. In the process aspect, service implementation is not yet optimal due to limited socialization, insufficient operator training, poor internet access, and underutilized service features. In the product aspect, only a portion of the community has felt direct benefits. Although positive impacts exist, they have not been widely felt. These findings highlight the need for improved human resources, stronger infrastructure, and broader socialization to ensure more effective and equitable village services through Gigades.id. Keywords: Evaluation, Village Services, Gigades.id Website